Whose policy uncertainty matters in the trade between Korea and the U.S.? - Mohsen Bahmani-Oskooee; Jungho Baek (Journal of Risk and Financial Management, 2021)
Since the introduction of the news-based policy uncertainty measure, a few studies have looked at its impact on trade flows by using panel models and aggregate trade data. In this paper we consider the short-run and long-run response of 61 2-digit U.S. exporting industries to Korea and 49 2-digit Korean exporting industries to the U.S. to policy uncertainty measures of the U.S. and Korea. We find that both measures have short-run effects on exports of almost one-third of industries in either direction. In the long run, however, while nine U.S. exporting industries (with a trade share of 9%) are negatively affected by the Korean uncertainty measure, only five industries (with 6% export share) are affected by the U.S. uncertainty measure. As for the Korean exporting industries, we find that three industries with a 31% export share are affected positively by the Korean uncertainty measure and six industries with a 7% export share are affected positively by the U.S. uncertainty measure.
Keywords: F14; F40; F50; 330; economic policy uncertainty; the U.S.; Korea; industry trade